Theoretical Study of Charge Transfer in Styryl Thiazilo Quinoxaline Dyes STQ-1, STQ-2,and STQ-3 in Organic Media System (Baghdad Science Journal, 2013)
Charge transfer in styryl dyes STQ-1, STQ-2,and STQ-3 with organic media system has been studied theoretically depending on the Franck- Condon rule and continuum dielectric model . The reorientation energies (eV) were evaluated theoretically depending on dipole momentum, dielectric constant , and refrective index n. The rate constant of charge transfer has been calculated depending on the reorientation energy (eV) ,effective free energy , potential height barrier , and coupling coefficient . A matlap program has been written to calculated the rate constant of charge transfer and other parameter. The results of calculations show that STQ-2 dye is more reaction for charge transfer compare with STQ-1 and STQ-3 dyes